Peranan Guru BK Dalam Mengembangkan Minat Dan Bakat Peseta Didik - Zulkarnain, Afdilla; Siregar, Mhd. Fuad Zaini (Invention: Journal Research and Education Studies, 2024)
Education is essentially a process from within to develop personality and abilities within and outside oneself. Developing interests and talents is one aspect of it. Interests and talents are key for students this paper is the result af qualitative descriptive research aimed at understanding the interests an talents of students. The research findings indicate thar interests and talents rafer to the understanfing outcames of students. The strategies applied by classroom teachers include incorporating interest and talent material into the learning contents, selecting appropriate methods and media, providing remedial support, fostering communication,setting examples,showing appreciation and knowledge, indentifying and selecting assistance programs. The competency of classroom teachers still needs to be enhanced so that students interests an taletants in learning can improve from the previous state. Menaging students significantly influences a students success in achieving their desires, hops, aspiration, and preparing themselves for life in society. This underscores the importance of student management within the scope of education. With effective management,schools can produce the desired students. Furthermore, student are the primary product of should manage them as effectively as possible to produce exceptional outcomes.